Clinical and Genetic Study on a Chinese Patient with Infantile Onset Epileptic Encephalopathy carrying a PPP3CA Null Variant: a case report - Yang, Sai (BMC Pediatr, 2020)
BACKGROUND: PPP3CA gene encodes the catalytic subunit A of a calcium-dependent protein phosphatase called calcineurin. However, two distinct mechanisms in PPP3CA deficiency would cause two clinically different diseases. Gain-of-function mutations in the autoinhibitory domain at the C-terminus would cause ACCIID that stands for arthrogryposis, cleft palate, craniosynostosis and impaired intellectual development. While loss-of-function mutations in PPP3CA would cause infantile or early childhood onset epileptic encephalopathy1, named as IECEE1. IECEE1 is a severe epileptic neurodevelopmental disorder and mainly characterized by psychomotor delay. Here, we report a Chinese patient who was clinically and genetically diagnosed as IECEE1. We also extensively analyzed electroencephalogram (EEG) features of the patient in this study. CASE PRESENTATION: A 2-year-old Chinese patient who had recurrent polymorphic seizures was clinically and genetically diagnosed as IECEE1. A frameshift variant c.1283insC (p.T429NfsX22) was identified in this case. Multiple types of abnormal features were observed in the EEG, comparing with the previous reports. CONCLUSIONS: These findings could expand the spectrum of PPP3CA mutations and might also support the diagnosis and further study of IECEE1.